Climate policy under socio-economic scenario uncertainty. (May 2016) - Drouet, Laurent; Emmerling, Johannes
Abstract: We study the role of uncertainty about the two main baseline drivers of the economy, namely population and GDP, for the determination of the optimal climate policy and the evaluation of policy costs. Firstly, we estimate the cost of baseline uncertainty from a decision maker's perspective using different metrics. Secondly, we discuss how measures of the costs of climate change induced impacts and climate policy costs can be compared under different and uncertain baseline assumptions. Given that policy costs and other measures such as impacts are typically expressed relative to GDP in a baseline, comparing those values with different baseline projections is not trivial. Finally, we compute the cost from baseline uncertainty which leads to a moderate increase of the welfare losses from climate change. Highlights: Uncertainty in climate-economy models also applies to GDP and population. The degree of such uncertainty can be assessed using several widely used metrics of uncertainty. To compute and compare policy costs, the CEBGE provides a useful general measure. Socio-economic uncertainty increases the welfare costs of climate change impacts.